The Italian Colonizing Activity 1870-1885 - زغير حزيم حسن (Al-Adab Journal, 2018)
The Italian colonizing activity started at the western coast of the Red Sea in Africa by the missionaries and geographical explorers, where the monch spiato reached to Assab and erect missionary centre. And after his return to Italy he encourage his government to occupy the region which made the government heir Robatino company to purchase Assab lands, which was part of colonizing goals which Italy sought. The British government oppose the Italian colonizing project at the beginning and consider this action passtracing to the Egyptian authority under the Ottoman colonizing where Britain by this stance sought Egyptian support in its invasion to Ethiopia. But as a result of the strategic and economical importance and the incapability of the Egyptian authority to control the area and for the growing of the French –British conflict on east Africa and for the patriotic resistance in Sudan against Britain. Britain was enforced to support Italian in this action at the western coast of the Red Sea to get the Italian support to get a clear image of the historical event we divided the thesis to three inquiries. The first tackled the beginning of Italian colonizing project, the second studied the global reject for the Italian project and the third tackled the British support to the Italian colonizing project.